2021
DOI: 10.1007/s11604-021-01195-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of advanced monoenergetic reconstruction technique in dual-energy computed tomography for detecting bladder cancer

Abstract: Purpose Detecting bladder cancer (BC) in routine CT images is important but is sometimes difficult when cancer is small. We evaluated the ability of 40-keV advanced monoenergetic images to depict BC. Materials and methods Fifty-two patients with a median age of 74 years (range 45–92) who were diagnosed as BC with transurethral resection or cystectomy, were included. They were examined with contrast-enhanced dual-energy CT (DE-CT) and advanced virtual mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The CT sensitivity in the detection of these tumors may be improved by the early enhancement as a diagnostic criterion [85]. Nakagawa et al [86], in fact, analyzed VMI at 40 keV of 52 patients with histological demonstration of bladder cancer in comparison with synthetics 120 kVp reconstructions and demonstrated that, in VMI at 40 keV, the difference in CT number between the cancer and bladder wall was significantly higher and that these images were preferred by the readers with a statistically significant difference.…”
Section: Study Of the Bladder And Uretersmentioning
confidence: 99%
“…The CT sensitivity in the detection of these tumors may be improved by the early enhancement as a diagnostic criterion [85]. Nakagawa et al [86], in fact, analyzed VMI at 40 keV of 52 patients with histological demonstration of bladder cancer in comparison with synthetics 120 kVp reconstructions and demonstrated that, in VMI at 40 keV, the difference in CT number between the cancer and bladder wall was significantly higher and that these images were preferred by the readers with a statistically significant difference.…”
Section: Study Of the Bladder And Uretersmentioning
confidence: 99%
“…However, the postoperative recurrence rate is high, up to 50% to 70%, which seriously endangers the life of sufferers. It is of great significance to watch an effective means to appraise the postoperative recurrence of bladder carcinoma for early clinical prevention and treatment and to improve the prognosis of sufferers [ 3 , 4 ]. Nuclear matrix protein 22 (NMP22) is an internal structural component of the nucleus, involved in DNA replication, transcription, and RNA synthesis, and also plays an important regulatory role in gene conveying.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative diagnosis can improve the accuracy of preoperative staging and detect the recurrence of bladder cancer after operation [ 24 26 ]. Conventional CT often uses two-dimensional slice observation, so many spatial data are lost, and the structural and morphological display of cancerous tissue is not complete and sufficient [ 27 ]. Imaging doctors cannot intuitively make accurate and objective judgments based on the observed images, which may lead to wrong diagnosis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%